2019
DOI: 10.1111/ijfs.14406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basil leaves and wheat bran water extracts on enzymatic browning of shredded storage iceberg lettuce

Abstract: Summary The impact of functional solutions (water infusions of radish sprouts, wheat bran (WBE), basil leaves (BLE) and lentil protein hydrolysate) on enzymatic browning of shredded iceberg lettuce was studied. BLE and WBE, limiting enzymatic browning in the highest degree, were tested during cold storage. The best inhibitors of PPO activity in lettuce stored for 8 days were 10% WBE (a decrease by 97%). POD activity was substantially decreased by ascorbic acid (by 75%) and 1% BLE (by 83%). POD and PPO inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…In contrast, Altunkaya & Gökmen [33] observed an opposite relationship during storage of fresh lettuce (Lactuca sativa). What is important, the increase in the phenolic content in the lettuce treated with the basil leaf extracts in the present study may also be explained by the fact that the extracts are rich in phenolics, mainly rosmarinic acid and quercetin derivates [9]. Llorach, Martinez-Sánchez, Tomás-Barberán, Gil, & Ferreres [34] reported that the antioxidant activity (DPPH or FRAP) of lettuce was highly correlated with the total phenolic content.…”
Section: Resultssupporting
confidence: 49%
See 4 more Smart Citations
“…In contrast, Altunkaya & Gökmen [33] observed an opposite relationship during storage of fresh lettuce (Lactuca sativa). What is important, the increase in the phenolic content in the lettuce treated with the basil leaf extracts in the present study may also be explained by the fact that the extracts are rich in phenolics, mainly rosmarinic acid and quercetin derivates [9]. Llorach, Martinez-Sánchez, Tomás-Barberán, Gil, & Ferreres [34] reported that the antioxidant activity (DPPH or FRAP) of lettuce was highly correlated with the total phenolic content.…”
Section: Resultssupporting
confidence: 49%
“…For preparation of the infusions, 10g of dried samples was mixed with 100 mL of boiling water and left to cool down. Then, the samples were centrifuged (15,000× g, 25 • C for 15 min), collected, diluted to working concentrations with water and used for the treatments [9].…”
Section: Preparation Of a Solution Of Inhibitors And Lettuce Treatmentmentioning
confidence: 99%
See 3 more Smart Citations